Event Marketing Implementation In Improving Brand Awareness of Indonesian Food Startup - Aprilia Prabawati; Meliza Meliza; Chaerani Agustin; Muhammad Aras (Syntax Corporation, 2022)
Culinary is not only a product consumed for daily needs, but it has become a lifestyle of the Indonesians. Many businesses in terms of culinary shows that culinary is a quite potential sector for local startups. PergiKuliner, engaged in food-related media based on website and application, provides directory information and reviews of places to eat. Intense competition with other food startups from abroad makes PergiKuliner as a local brand need to improve its brand awareness so that it is better known by the Indonesians for recommendations of good places to eat. This study aims to determine the Marketing Communications strategy of PergiKuliner in improving brand awareness through event marketing. The research approach used was descriptive qualitative. Research data were collected through direct observation and in-depth interviews with the CEO and Marketing Communication division of PergiKuliner. The results showed that the event marketing strategy was conducted by PergiKuliner to improve its brand awareness by holding offline events, such as PergiKuliner Festival (culinary bazaar) and PergiKuliner Berburu (restaurant hunting). The factors that need to be considered in implementing an event marketing were a selection of theme that is currently being discussed by the public, selection of tenants that are following the theme, selection of venue with good traffic, good marketing communications within the internal team, and gimmicks to attract visitors' attention.